Validation of Whole Slide Imaging for primary surgical pathology diagnosis of prostate biopsies - Vidya Rao; Pavitra Subramanian; Akash P Sali; Santosh Menon; Sangeeta B Desai (Wolters Kluwer Medknow Publications, 2021)
Context: Whole slide imaging (WSI) is an important component of digital pathology which includes digitization of glass slides and their storage as digital images. Implementation of WSI for primary surgical pathology diagnosis is evolving, following various studies which have evaluated the feasibility of WSI technology for primary diagnosis. Aims, Settings and Design: The present study was a single-center, observational study which included evaluation by three pathologists and aimed at assessing concordance on specialty-specific diagnosis and comparison of time taken for diagnosis on WSI and conventional light microscopy (CLM). Materials and Methods: Seventy prostate core biopsy slides (reported between January 2016 and December 2016) were scanned using Pannoramic MIDI II scanner, 3DHISTECH, Budapest, Hungary, at 20× and 40×. Sixty slides were used for validation study following training with 10 slides. Statistical Analysis Used: Intraobserver concordance for diagnosis between the two platforms of evaluation was analyzed using Cohen's κ statistics and intraclass correlation coefficient (ICC); observation time for diagnosis was compared by Wilcoxon signed-rank test. Results: Interpretation on WSI using 20× and 40× was comparable with no major discordance. A high level of intraobserver agreement was observed between CLM and WSI for all three observers, both for primary diagnosis (κ = 0.9) and Grade group (κ = 0.7-0.8) in cases of prostatic adenocarcinoma. The major discordance rate between CLM and WSI was 3.3%-8.3%, which reflected the expertise of the observers. The time spent for diagnosis using WSI was variable for the three pathologists. Conclusion: WSI is comparable to CLM and can be safely incorporated for primary histological diagnosis of prostate core biopsies.